The Shifting Role of Teachers in Digital-Based Learning: A Literature Review with Bibliometric Analysis (2020–2024) - Muhammad Rizqy; Bayu Hadiatma Fasya; Miftahul Jannah; Nina Nisrina (Indonesian Journal of Teacher Education, 2025)
This study aims to analyze research trends regarding the shifting role of teachers in digital-based learning through a bibliometric approach. The methods used are descriptive and analytical, utilizing the Publish or Perish application to collect data from Google Scholar and VOSviewer to analyze and visualize the data. The analyzed data consist of 61 scientific articles from the years 2020–2024 that underwent a selection process based on predetermined criteria. The results indicate an increase in the number of publications, particularly in 2024, suggesting growing attention to the transformation of teachers’ roles in digital learning. VOSviewer analysis reveals that the research is dominated by the interconnection between the concepts of the teacher’s role, facilitator, and digital learning within an interconnected network. Furthermore, an examination of the most highly cited articles reveals that the teacher’s role is shifting from that of a demonstrator to a facilitator who guides and supports more active and self-directed learning. Thus, digital-based learning not only impacts technology use but also drives a fundamental transformation of the teacher’s role. Consequently, strengthening teachers’ competencies—particularly in digital literacy and innovative learning strategies—is essential to support effective learning in the digital age.